Postsymbolistisches Schreiben. Studien zur Poetik des Akmeismus und Osip Mandel'štams - Werberger, Annette (Slavistische Beitraege, 2005)
Since Žirmunskij the acmeists have been considered "overcomers of symbolism", which has led to many misunderstandings about the acmeist poetics. While the symbolists discovered the ambiguity of the word as the basis of metaphor, the acmeists are more aware of the connection between identity and plurality of the word. They understand the idea of ​​a complete independence of the poetic language from everyday language as an illusion and danger and sustainably pragmatic symbolist understanding of the language. Acmeistic writing tries to referentle to different levels and to create a kind of "new realism of writing". In their texts, the acmeists try to regain authenticity and reality through a greater temporal-spatial and cultural contextualization, the inclusion of reality substrates, greater involvement of everyday language, dialogical expressions, taking up a historical design language or a narrative Parlandogestik. - The work also offers a brief view of the reception of acmeism by Brodskij, Celan and Grünbein.